2015
DOI: 10.1177/0271678x15617953
|View full text |Cite
|
Sign up to set email alerts
|

Crossed cerebellar diaschisis in patients with acute middle cerebral artery infarction: Occurrence and perfusion characteristics

Abstract: We aimed to investigate the overall prevalence and possible factors influencing the occurrence of crossed cerebellar diaschisis after acute middle cerebral artery infarction using whole-brain CT perfusion. A total of 156 patients with unilateral hypoperfusion of the middle cerebral artery territory formed the study cohort; 352 patients without hypoperfusion served as controls. We performed blinded reading of different perfusion maps for the presence of crossed cerebellar diaschisis and determined the relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 46 publications
5
36
3
Order By: Relevance
“…Recent studies on CCD occurrence and perfusion characteristics suggest that CT perfusion is an appropriate technique to study the phenomenon of CCD. 14,15 Building on this, we could show that the mere presence of CCD in the acute phase has no impact on functional outcome in ischemic stroke patients. The original notion of diaschisis being a reversible condition, either in the form of CCD or transhemispheric diaschisis, 43 is not contradicted by our observations as significant clinical improvement was observed in patients with acute CCD.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Recent studies on CCD occurrence and perfusion characteristics suggest that CT perfusion is an appropriate technique to study the phenomenon of CCD. 14,15 Building on this, we could show that the mere presence of CCD in the acute phase has no impact on functional outcome in ischemic stroke patients. The original notion of diaschisis being a reversible condition, either in the form of CCD or transhemispheric diaschisis, 43 is not contradicted by our observations as significant clinical improvement was observed in patients with acute CCD.…”
Section: Discussionmentioning
confidence: 84%
“…30 Advances in imaging technology meanwhile allow to cover the entire brain tissue at a reasonable radiation dose (whole-brain CT perfusion, WB-CTP). 31 While recent WB-CTP studies on stroke patients have shown the occurrence of CCD in the acute phase to be dependent on the location of the supratentorial perfusion deficit and the severity of supratentorial hypoperfusion, 14 the key question of the clinical impact of CCD in acute ischemic stroke remains unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanism for GM atrophy in ipsilesional cerebellar cortex cannot be explained by axonal degeneration through crossed fibres as all lesions located at the same side as cerebellum. We speculated that depression of metabolism at the non‐ischaemic side of hemisphere may result in GM atrophy in the ischaemic side of cerebellum, which was similar to the phenomenon of crossed cerebellar diaschisis (Mah et al ., ; Sommer et al ., ). Further investigation is still required to verify this speculation.…”
Section: Discussionmentioning
confidence: 97%
“…CCD mostly accompanies middle cerebral artery infarctions. Sommer et al (4) found CCD in 35.3% of patients with middle cerebral artery infarction. In particular, it was found to be associated with hypoperfusion involving the left hemisphere, frontal lobe, and thalamus.…”
Section: Dear Editormentioning
confidence: 97%
“…Damage of corticopontocerebellar fibers is usually secondary to cerebral hypoperfusion, but it can also be related with supratentorial hyperperfusion following revascularization (3). Scientific data show that disruption in corticopontocerebellar fibers causes functional deactivation by leading decrease in excitatory input and a decrease in cerebellar blood flow (4).…”
Section: Dear Editormentioning
confidence: 99%